Effect of Inorganic Nitrate on Exercise Capacity in Heart Failure With Preserved Ejection Fraction. Issue 4 (27th January 2015) - Zamani, Payman; Rawat, Deepa; Shiva-Kumar, Prithvi; Geraci, Salvatore; Bhuva, Rushik; Konda, Prasad; Doulias, Paschalis-Thomas; Ischiropoulos, Harry; Townsend, Raymond R.; Margulies, Kenneth B.; Cappola, Thomas P.; Poole, David C.; et al.
<x xml:space="preserve">Abstract</x> Background— Inorganic nitrate (NO3−), abundant in certain vegetables, is converted to nitrite by bacteria in the oral cavity. Nitrite can be converted to nitric oxide in the setting of hypoxia. We tested the hypothesis that NO3− supplementation improves exercise capacity in heart failure with preserved ejection fraction via specific adaptations to exercise. Methods and Results— Seventeen subjects participated in this randomized, double-blind, crossover study comparing a single dose of NO3-rich beetroot juice (NO3−, 12.9 mmol) with an identical nitrate-depleted placebo. Subjects performed supine-cycle maximal-effort cardiopulmonary exercise tests, with measurements of cardiac output and skeletal muscle oxygenation. We also assessed skeletal muscle oxidative function. Study end points included exercise efficiency (total work/total oxygen consumed), peak <inline-graphic xlink:href="ark:/27927/pgh3sztrtmc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> O2, total work performed, vasodilatory reserve, forearm mitochondrial oxidative function, and augmentation index (a marker of arterial wave reflections, measured via radial arterial tonometry). Supplementation increased plasma nitric oxide metabolites (median, 326 versus 10 μmol/L; P=0.0003), peak <inline-graphic xlink:href="ark:/27927/pgh3sztrt2j" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> O2 (12.6±3.7 versus 11.6±3.1 mL O2·min−1·kg−1; P=0.005), and total work performed (55.6±35.3 versus 49.2±28.9 kJ; P=0.04). However, efficiency was unchanged. NO3− led to greater reductions in systemic vascular resistance (−42.4±16.6% versus −31.8±20.3%; P=0.03) and increases in cardiac output (121.2±59.9% versus 88.7±53.3%; P=0.006) with exercise. NO3− reduced aortic augmentation index (132.2±16.7% versus 141.4±21.9%; P=0.03) and tended to improve mitochondrial oxidative function. Conclusions— NO3− increased exercise capacity in heart failure with preserved ejection fraction by targeting peripheral abnormalities. Efficiency did not change as a result of parallel increases in total work and <inline-graphic xlink:href="ark:/27927/pgh3sztrt79" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> O2. NO3− increased exercise vasodilatory and cardiac output reserves. NO3− also reduced arterial wave reflections, which are linked to left ventricular diastolic dysfunction and remodeling. Clinical Trial Registration— URL: www.clinicaltrials.gov. Unique identifier: NCT01919177.